The river of time - Novikov, I. D. (Igorʹ Dmitrievich) (Cambridge University Press, 1998)
"Can we change the past?" "The surprising answer to this question can be found in the final chapters of this book." "Examining both the history of the study of time, from the classical Greeks through to the present day, and presenting in detail the modern state of physical research on the subject, this book is a superb overview of a fascinating subject." "The figures who have helped to shape our views on time are presented as real people, in the context of their own times and struggles: from Socrates' troubles in Athens, to the experiences of physicists under the old Soviet Union. In addition Novikov details his personal experiences with great Russian and Western physicists, such as Sakharov, Zeldovich, Rees and Hawking, and his travels in the West before the fall of the Iron Curtain."--Jacket.